The book eaters - Dean, Sunyi (New York : Tor, 2022)
It's a story of motherhood, sacrifice, and hope; of queer identity and learning to accept who you are; lies and the danger of believing the narratives others create for you. Out on the Yorkshire Moors lives a secret line of people for whom books are food, and who retain all of a book's content after eating it. Devon is part of The Family, an old and reclusive clan of book eaters. Her brothers grow up feasting on stories of valor and adventure, and Devon-like all other book eater women-is raised on a carefully curated diet of fairytales and cautionary stories. But real life doesn't always come with happy endings.
"A Tom Doherty Associates book."
Keywords: Books and reading -- Fiction; Clans -- Fiction; Food -- Fiction; Mothers and sons -- Fiction; Great Britain -- Fiction; Fantasy fiction; Science fiction